Transgenic animals as artificial organisms - Bota Arqué, Alexandre (Acta Bioethica, 2007)
The possibility of genetic modification of living organisms has generated ethical questions of difficult solution. The searching for conceptual frames has put into question whether the ontological status of organisms altered by biotechnology has been changed. This paper approaches the biotechnological organism following the thinking of philosophers Ortega y Gasset and Xavier Zubiri, based on their view on anthropology and technology conceptualizing the biotechnological artificial object as an "artificial organism", with the particularity that it is the first object produced by human beings which reproduces independently.